Cellular energy allocation and scope for growth in the estuarine mysid Neomysis integer (Crustacea: Mysidacea) following chlorpyrifos exposure: a method comparison - Verslycke, T.; Roast, S. D.; Widdows, J.; Jones, M. B.; Janssen, C. R. (Journal of Experimental Marine Biology and Ecology, 2004)
Mysids (Crustacea: Mysidacea) are used routinely in acute toxicity testing to evaluate the comparative toxicity of chemicals to aquatic organisms. The need for sublethal endpoints that provide comprehensive understanding of the potential impacts of toxicants to natural populations has resulted in examination of several physiological responses in mysid shrimp, including scope for growth (SFG) and cellular energy allocation (CEA). Both assays, based on the concept that energy in excess of that required for normal maintenance will be available for growth and reproduction, have been reported independently for the mysid Neomysis integer. The present study compares the responses of N. integer following exposure to environmentally realistic concentrations of the organophosphate pesticide chlorpyrifos using both assays. Oxygen consumption in the SFG assay was significantly correlated with cellular respiration rate in the CEA assay, and both were significantly increased by chlorpyrifos exposure. In addition, the protein, sugar, lipid and total energy content in the CEA assay and the egestion rate in the SFG assay were significantly different in chlorpyrifos-exposed mysids compared with control mysids. In contrast, absorption efficiency in the SFG assay was unaffected by pesticide exposure. Significant effects in the SFG and CEA assays were more pronounced following short (i.e. 48 h) compared with longer exposure periods (e.g. 168 h). SFG was significantly reduced at near-lethal concentrations (0.072 and 0.100 g chlorpyrifos l?1), whereas CEA was reduced in all chlorpyrifos-exposed mysids (0.038, 0.056, 0.072 and 0.100 g chlorpyrifos l?1) although there was no concentration response.
NeMys doc_id: 11001 NeMys doc_id: 11005